Isolation of estuarine biosurfactant-producing bacteria - Domingues, Patrícia Maia (2013)
Bioremediation has proven to be an effective strategy in the recuperation of oil contaminated ecosystems. However most bacteria used in this processes, while being able to degrade a wide range of the oil hydrocarbons, have limited action due to the low water solubility of these compounds. Hence, a possible solution for this problem would be the use of biosurfactant-producing bacteria, since the presence of surfactants help improve the hydrocarbons dispersal, solubilization and bioavailability. The objective of this work was to assess the biotechnological potential of Ria de Aveiro estuarine system regarding the presence of hydrocarbonoclastic biosurfactant-producing bacteria and to evaluate different combinations of environmental inocula and carbon sources for the isolation of biosurfactants producing bacteria. Selective cultures (diesel, crude and paraffin) were prepared using inocula from different environmental matrixes: samples from the surface microlayer (SML), bulk estuarine sediments and sediments of the rhizosphere of Halimione portulacoides, a characteristic halophyte from the salt marshes of Ria de Aveiro. During the incubation period, the development of the selective cultures was assessed by quantification of colony forming units (CFU). The highest value of CFU was obtained in the crude-sediment culture, while the lowest value was found with the diesel-rhizosphere combination. The DGGE profiles of the 16s rRNA gene fragments of the total community DNA extracted at the end of the incubation of the selective cultures, show that communities were different in terms of structural diversity. The values of the Shannon-Weaver index of diversity indicate that the higher diversity was achieved in the selective cultures with paraffin as carbon source (2.5231), followed by the crude oil (2.2509), and diesel (1.6726) selective cultures. From the selective cultures, 111 presumably hydrocarbonoclastic isolates were obtained after isolation and purification. Of these, 66 were tested for biosurfactant production by the atomized oil assay, with positive results for 17 isolates (25.8%). The environmental matrix with best results was the SML water and diesel was the most effective carbon source. Having in consideration the high number of isolates obtained from the selective cultures and the percentage of biosurfactant producers, the estuarine system of Ria the Aveiro, and in particular the SML, can be regarded as an interesting seedbank for the prospection of hydrocarbonoclastic and biosurfactants producing bacteria. The SML microhabitat shows particularly high biotechnological potential for the isolation of bacterial strains with interesting properties for application in bioremediation strategies in coastal and estuarine areas.